Agricultural Credit Market and Farmers’ Response: A Case Study of Turkey - Erdogan Gunes; Hormoz Movassaghi (Turkish Journal of Agriculture: Food Science and Technology)
Agriculture is an important sector in Turkey’s economy. Access to credit financing is critical for timely acquisition of different inputs, farm productivity, and ultimately farmers’ financial well-being. Historically, Ziraat Bank and Agricultural Credit Cooperatives, supported by Turkish government, have been the principle supplier of loanable funds in the agricultural sector. However, since 2000, many private banks have discovered the potential of this market and entered the competition. This study was designed to investigate the structure of the agricultural credit market in Turkey and identify factors that influence farmers’ preference among alternative lenders. It was found that although the 550 Turkish farmers surveyed had several options among lenders, low interest rates and attainable eligibility criteria emerged as the most important differentiators among banks. Results from the Analytic Hierarchy Process (AHP) demonstrate the rising role of private banks’ credit. However, Ziraat Banks’ subsidized credits still dominant and its composite weight is 30.74% of total amount of agricultural credit market.